2019
DOI: 10.1111/1750-3841.14442
|View full text |Cite
|
Sign up to set email alerts
|

Quality Parameters of Masa and Tortillas Produced from Blue Maize (Zea mays sp. mays) Landraces

Abstract: There is increasing interest in the production of landrace blue maize varieties for the production of traditional foods and for specialty (noncommodity) products. Most varieties have soft (floury) endosperm and their suitability for thermo-alkaline processing is not known. We examined the physical and functional properties of eight floury varieties with those of three dent and one flint variety for masa and tortilla production. Results revealed high variability in physical properties of kernels. Significant di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 37 publications
0
5
0
1
Order By: Relevance
“…The 2% steep treatment, possibly due to the overnight moisture absorption time, as well as residual rinse water, had a significantly higher moisture content of around 48%, which is similar to moisture values in nixtamalized corn masa. Chimimba et al (2019), for example, reported a moisture range for corn masa from 47.2% to 56.0%.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The 2% steep treatment, possibly due to the overnight moisture absorption time, as well as residual rinse water, had a significantly higher moisture content of around 48%, which is similar to moisture values in nixtamalized corn masa. Chimimba et al (2019), for example, reported a moisture range for corn masa from 47.2% to 56.0%.…”
Section: Resultsmentioning
confidence: 99%
“…The 2% steep treatment, possibly due to the overnight moisture absorption time, as well as residual rinse water, had a significantly higher moisture content of around 48%, which is similar to moisture values in nixtamalized corn masa. Chimimba et al (2019), for example, reported a moisture range for corn masa from 47.2% to 56.0%. The adhesiveness values for the three no-steep masas were not significantly different from one another, even with increasing lime levels, whereas the 2% steep treatment was significantly more adhesive than the 1% and 1.5% NS masas.…”
Section: Masa and Tortilla Physical Propertiesmentioning
confidence: 99%
“…Conversely, dent and flint varieties of flours had the greatest enthalpy values due to a more organized kernel structure. Rheological and thermal parameters indicated that generally the Southwest floury varieties are more suitable for tortilla production [131]. The traditional nixtamalization and lime-cooking extrusion process more markedly decreased carotenoids concentration and the oxygen radical absorbance capacity (ORAC) in red Mexican pigmented corns than in yellow varieties.…”
Section: Colored Corn-based Foods and Technological Aspectsmentioning
confidence: 99%
“…In contrast, flour kernels must be carefully defended from insects and other animals, and they are prone to spoilage. However, traditional southwestern floury landraces are more suitable for making maize breads because they are easily ground and their starch pasting (cook time) and gelatinization properties make them ideal for tortilla making (Chimimba et al 2019). Dent kernels, composed of both flint and flour endosperm, would offer the advantages of both.…”
Section: Cultural Significance Of Maize Kernel Colormentioning
confidence: 99%